2010
DOI: 10.1179/016164110x12645013515052
|View full text |Cite
|
Sign up to set email alerts
|

The expression of mismatch repair proteins MLH1, MSH2 and MSH6 correlates with the Ki67 proliferation index and survival in patients with recurrent glioblastoma

Abstract: Our results indicate a potential important role of MLH1 and MSH6 in glioblastoma progression. Specific attention should be given on the role of MLH1 and MSH6 in patients with glioblastoma recurrence during temozolomide treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…In line with our immunohistochemical findings, Stark et al 30 recently reported on reduced immunoreactivity for MLH1 in recurrent compared to primary glioblastomas. Other authors determined the mRNA expression levels of MSH2, MLH1, PMS1, PMS2 and GTBPT in gliomas and found lower expression relative to normal lymphocytes in variable subsets of patients.…”
Section: Clinical Implications For Mgmt Promoter Methylation Testingsupporting
confidence: 93%
“…In line with our immunohistochemical findings, Stark et al 30 recently reported on reduced immunoreactivity for MLH1 in recurrent compared to primary glioblastomas. Other authors determined the mRNA expression levels of MSH2, MLH1, PMS1, PMS2 and GTBPT in gliomas and found lower expression relative to normal lymphocytes in variable subsets of patients.…”
Section: Clinical Implications For Mgmt Promoter Methylation Testingsupporting
confidence: 93%
“…Single-locus MSI was observed in only 3% of glioma patient samples with MSH6 loss, while no sample was classified as MSI-high. This result indicated that the expression of MSH6 was not associated with MSI (11), which has been confirmed by other studies (5,7,9). The inactivation of MSH6 is only associated with the MSI-low phenotype, but not with MSI-high (7).…”
Section: Somatic Msh6 Mutations Glioma Recurrence and Drug Resistancesupporting
confidence: 77%
“…Growing evidence indicates that a deficiency of MMR genes is associated with the recurrence and drug resistance of glioma. Candidate genes of interest include mutL homolog (MLH)1, mutS homolog (MSH)2 and MSH6 (4,5). In particular, MSH6 mutations are considered to play an important role in the recurrence of glioma, acquired resistance to alkylating agents and genome instability (3,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Second, two studies have shown by immunohistochemistry that small subpopulations of MLH1-negative cells commonly arise in primary GBM. One study showed that MLH1-negative cells were enriched after TMZ treatment in recurrent tumors (Stark et al 2010). The second study showed that cells lacking PMS2 were enriched in recurrent tumors (Felsberg et al 2011).…”
Section: Discussionmentioning
confidence: 99%